Antioxidant Effect of Ziziphus vulgaris, Portulaca oleracea, Berberis integerima and Gundelia tournefortti on Lipid Peroxidation, Hb Glycosylation and Red Blood Cell Hemolysis - A Movahedian Ataar; A Eshraghi; S Asgari; Gh Naderi; A Badiee (Institue of Medicinal Plants, ACECR, 2011)
Background: Oxidative damage may play a role in the development of atherosclerosis and diabetes mellitus. Antioxidant could help to protect against oxidative stress related disorders. Objective: We studied the antioxidant effects of some plants, namely, Ziziphus vulgaris, Portulaca oleracea, Berberis integerima, Gundelia tournefortti on the above mentioned reactions. Methods: Ethanolic and water extracts of the mentioned plants were prepared in three different concentrations: 2.5, 5 and 10 µg/ml. Hepatocytes of rat were exposed to AAPH. The amount of Serum glutamate oxaloacetate transferase )SGOT( released from membrane lipid peroxidation was also measured in presence and absence of the plant extract. The changes of hemoglobin (Glycosylation( and red blood cell hemolysis were measured in the presence and absence of the extract. The percent of oxidation inhibition was compared with that in control subjects. Results: The results showed all plants had antioxidant effects on hemolysis of red blood cell. The highest extent of hemolysis inhibition of red blood cell was due to Ziziphus. The highest glycosylation inhibition of hemoglobin was shown by Gundelia and Berberis. Portulaca, Gundelia and Berberis decreased SGOT release from hepatocytes, but the least extent of lipid peroxidation inhibition was shown by Ziziphus. Conclusion: This study showed that the plants have an antioxidant effect and they can be probably used as an antioxidant in food supplement in diabetic, atherosclerotic and liver disease patients.